Cuproplasia and cuproptosis, two sides of the coin - Kaizhong Lu; Chandra Sugiarto Wijaya; Qinghua Yao; Hongchuan Jin; Lifeng Feng (Cancer Communications)
Abstract Copper is an essential micronutrient in the human body, mainly acting as a crucial cofactor required for a wide range of physiological processes across nearly all cell types. Recent advances revealed that tumor cells seize copper to fulfill their rapid proliferation, metastasis, immune evasion, and so on by reprogramming the copper regulatory network, defined as cuproplasia. Thus, targeting copper chelation to reduce copper levels has been considered a rational tumor therapy strategy. However, overloaded copper ions could be toxic, which leads to the aggregation of lipoylated mitochondrial proteins and the depletion of iron‐sulfur clusters, ultimately resulting in cell death, termed cuproptosis. Upon its discovery, cuproptosis has attracted great interest from oncologists, and targeting cuproptosis by copper ionophores exhibits as a potential anti‐tumor therapy. In this review, we present the underlying mechanisms involved in cuproplasia and cuproptosis. Additionally, we sum up the chemicals targeting either cuproplasia or cuproptosis for cancer therapy. Further attention should be paid to distinguishing cancer patients who are suitable for targeting cuproplasia or cuproptosis.